ANALISIS PENGARUH KUALITAS PELAYANAN BERBASIS BUDAYA ORGANISASI TERHADAP KEPUASAN PENGGUNA JASA FASILITAS KAWASAN BERIKAT PADA BEA CUKAI MAGELANG - Subroto Wisnu Wardana; Florentina Ratih Wulandari; Rino Ardhian Nugroho (Halu Oleo University, 2024)
The aim of the research is to examine, determine and analyze the influence of service quality based on organizational culture on the satisfaction of users of Bonded Zone facility services at Magelang Customs. The method used is a quantitative method with a descriptive statistical approach. Research data at Magelang Customs. was obtained using a questionnaire and a sample of 49 respondents. The data analysis carried out in the research is statistical and mathematical methods through GAP Analysis, Customer Satisfaction Index (CSI), and Importance-Performance Analysis (IPA) measurements. The results of research on Service Quality calculations using GAP Analysis show that there are indicators from statement items that have negative values from the GAP Analysis calculations for each dimension of service quality with the total score obtained being -0.20. This value shows that the expectation score is greater than the performance score. Data analysis using the Customer Satisfaction Index (CSI) at Magelang Customs showed that 89.12% were very satisfied. The overall level of customer satisfaction by looking at the level of performance and level of importance of product or service attributes as measured using the Customer Satisfaction Index (CSI) at the Magelang Customs, overall expectations and performance are very good. Then, the results of the Importance-Performance Analysis (IPA) measurement show improvements in service quality which are focused on 5 indicators that are included in important services, but satisfaction is still low.